CDC’s Efforts to Quantify Prescription Opioid Overdose Deaths Fall Short - Peppin, John F. (Pain Ther, 2021)
In a 2018 report titled, Quantifying the Epidemic of Prescription Opioid Overdose Deaths, four senior analysts of the Centers for Disease Control and Prevention (CDC), including the head of the Epidemiology and Surveillance Branch, acknowledged for the first time that the number of prescription opioid overdose deaths reported by the CDC in 2016 was erroneous. The error, they said, was caused by miscoding deaths involving illicitly manufactured fentanyl (IMF) as deaths involving prescribed fentanyl. To understand what caused this error, the authors examined the CDC’s methodology for compiling drug-related mortality data, beginning with the source data obtained from approximately 2.8 million death certificates received each year from state vital statistics registrars. Systemic problems often begin outside the CDC, with a surprisingly high rate of errors and omissions in the source data. Using the CDC’s explanation for what caused the error, the authors show why an international program used by the CDC for reporting mortality is ill-suited for compiling and reporting drug overdose deaths. Except for heroin, methadone, and opium, each of which has an individual program code, all other opioids are separated in just two program codes according to whether they are synthetic or semisynthetic/opiates. Methadone-involved deaths pose a special problem for the CDC because methadone has dual indications for treating pain and for treating opioid use disorder (OUD). In 2019, more than seven times more methadone was administered or dispensed for OUD treatment than was prescribed for pain, yet all methadone-involved deaths are coded by the CDC as involving the prescribed form of the drug. The authors conclude that the CDC was at fault for failing to recognize and correct this problem before 2016. Public policy consequences of this failure are briefly mentioned.